An assessment on the implementation of adolescent reproductive health program in the prevention of induced abortion among senior high school students in secondary schools of Tetuan District, Zamboanga City - Dionio, Cynthia A.
Induced abortion is the result of unwanted pregnancy which lead to maternal deaths among adolescents which need to be addressed immediately through the ARH Program Implementation in the school thus improving their knowledge in the prevention of induced abortion. In Zamboanga City, FHSIS report CY 2009 the number one cause of death is abortion. Our commitment to Millennium Development Goal is to improve maternal health and reduce infant death so with this activity we can be able to find better strategies in preventing unwanted pregnancy that lead to induced abortion thus, reducing maternal and infant death. Using a cross-sectional study design, a sample of 661 senior students from the public and private high schools of District Tetuan, Zamboanga City through simple random sampling from the list of students in said schools which also include the ARH Coordinator and ARH lecture handling the ARH subject regarding the knowledge of the senior student and ARH Coordinator and the ARH Program especially the prevention of induced abortion. For the knowledge of the senior student on the functionality of ARH Program the result was low level of knowledge on ARH Clinic functionality as well as on the implementation of the ARH Policy 93% and 84% respectively. On the knowledge of the student on the prevention of induced abortion, 81.75% had an adequate knowledge. Conclusion: The senior high school students of Tetuan District, Zamboanga City have an inadequate knowledge on the prevention of induced abortion and also a low level of knowledge on the functionality of ARH Program as well as the implementation of ARH Policy in the School.